Analysis of Nonlinear Dynamics Characteristic of Spur Gear Pair System with Fault - Wang Yongliang; Wan Yanjing; Yin Fengwei; Yang Liu (Jixie chuandong)
The nonlinear dynamics model for a spur gear pair system is established where the mild wear and crack faults are considered. The nonlinear dynamics equations with faults are solved by employing 4~5 order variable step size Runge-Kutta method. The bifurcation diagrams， phase portraits and Poincaré maps of the single-stage gear system under the condition of no fault, mild wear fault and crack fault are obtained to research the nonlinear dynamics characteristic of system. The dynamics behaviors of gear system in fault-free and fault are studied. The conclusions provide theoretical reference for fault diagnosis, dynamic design and safe operation of gear system.